Potensi Antioksidan Fraksi Ekstrak Daun Krangkungan Hasil Optimasi Pelarut dan Waktu Sokletasi dengan Metode DPPH - Nova Rahma Widyaningrum; Yesi Ihdina Fityatal Hasanah; Kiki Puspitasary; Mella Santika Azhari; Sitta Hasanattin Sholehah (Fakultas Farmasi Universitas Setia Budi, 2026)
The content of Ipomoea carnea Jacq leaves includes flavonoids, saponins, phenolics and alkaloids, which can be used as anti-inflammatory, antioxidant, antidiabetic, antimicrobial, wound healing, immunomodulator, cardiovascular treatment, embryotoxic and antifungal. The purpose of this study was to examine the antioxidant potential derived from the optimal fraction of the extraction solvent and soxhletation time using the DPPH method. Extraction of the contents of krangkungan leaves was carried out with methanol solvent for 5 hours, then fractionation was carried out using n-hexane, ethyl acetate and methanol solvents and then tested for potential antioxidant activity using the DPPH method. Activity measurements were carried out using a UV-VIS spectrophotometer with a wavelength of 526.4nm. The antioxidant results showed that all fractions had antioxidant activity, but had different categories. The IC50 values ​​of n-hexane were 115.125 ppm (moderate), ethyl acetate 82.804 ppm (strong), and methanol 51.63 ppm (strong) respectively, with a routine comparator of 24.23 ppm (very strong). The results of statistical analysis using the ANOVA test showed significant differences between the three fractions and the routine comparator.